In silico identification of essential transmembrane proteins in Salmonella typhimurium as potential drug and vaccine targets - Mohd Samsidi, Izzati Nasuha; Zulkiply, Nawal; Abd Rashid Syaida, Anati; Raja Yahya, Mohd Fakharul Zaman (Faculty of Applied Sciences, 2025)
Salmonella sp. is a globally prevalent organism responsible for causing salmonellosis, a foodborne illness. Salmonella typhimurium is a strain of Salmonella sp. that is not associated with typhoid fever but can cause gastrointestinal inflammation and severe infection. Despite advancements in genomic and proteomic technologies, several proteins identified in S. typhimurium remain uncharacterized. Thus, the objective of the present study was to characterize the transmembrane proteins of S. typhimurium that could serve as potential drug and vaccine targets. In this study, 150 uncharacterized proteins from S. typhimurium were randomly selected from UniProtKB and analyzed using PSORTb V3.0.3 and TMHMM. Identified transmembrane proteins were further analyzed using DEG, BLASTp, ProtParam, ScanProsite, STRING 12.0, and VaxiJen 2.0. The results indicated that 32 uncharacterized proteins (21%) were predicted to be transmembrane proteins involved in various biological pathways. Among these transmembrane proteins, protein A0A2J0RKS1 was predicted to be essential, antigenic, and non-host homologous, suggesting its potential as a drug and vaccine target for combating salmonellosis. This study underscores the potential of computational biology in drug target discovery, particularly against pathogens like S. typhimurium.